Two mutually complementary synthetic approaches towards 3-substituted 3,4-disubstituted and 1-(2-pyridyl)-substituted isoquinolines - I. L. Nikonov; D. S. Kopchuk; A. F. Khasanov; A. P. Krinochkin; E. S. Starnovskaya; Ya. K. Shtaiz; M. I. Savchuk; O. S. Tanya; G. V. Zyryanov; V. L. Rusinov; O. N. Chupakhin (Chimica Techno Acta, 2018)
Two mutually complementary synthetic approaches towards 3- and 3,4-disubstituted 1-(2-pyridyl) isoquinolines were studied. The aryne-based method was successfully used for the obtaining of the corresponding the 3-cyano-1-(2-pyridyl)isoquinolines in one step/pot reaction, while it is unacceptable for the obtaining of other 1-(2-pyridyl)isoquinolines. The enamine-based approach was successfully applied for the synthesis of other 1-(2-pyridyl)isoquinolines, while it was  unacceptable for the obtaining of  3-cyano-1-(2-pyridyl)isoquinolines.